2023
DOI: 10.1172/jci157515
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of food intake by Glp1r/Lepr-coexpressing neurons prevents obesity in mouse models

Abstract: The adipose-derived hormone leptin acts via its receptor (LepRb) in the brain to control energy balance. A potentially unidentified population of GABAergic hypothalamic LepRb neurons plays key roles in the restraint of food intake and body weight by leptin. To identify markers for candidate populations of LepRb neurons in an unbiased manner, we performed single-nucleus RNA-Seq of enriched mouse hypothalamic LepRb cells, identifying several previously unrecognized populations of hypothalamic LepRb neurons. Many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Rupp et al demonstrated that neurons in the dorsomedial hypothalamus (DMH) exhibit sensitivity to both leptin and liraglutide 43 . They further found that the reactivation of glp1r , specifically in neurons expressing the leptin receptor, was adequate for liraglutide to effectively suppress food intake.…”
Section: Discussionmentioning
confidence: 99%
“…Rupp et al demonstrated that neurons in the dorsomedial hypothalamus (DMH) exhibit sensitivity to both leptin and liraglutide 43 . They further found that the reactivation of glp1r , specifically in neurons expressing the leptin receptor, was adequate for liraglutide to effectively suppress food intake.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is foreseeable that the effect of GLP-1RA improves first-phase insulin secretion and offsets zthe high DPP-4 levels, which lead to reduced glucose level, reduced weight, a lower body adiposity index, and an improved lipid profile ( 14 ). Finally, the possibility of GLP-1 to work as a leptin sensitizer centrally may be an important contributor ( 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…To investigate neurons that co-express Lepr , Glp1r, and Slc32a1, such as the Trh Arc neurons described here, a recent study used conditional knock-out and rescue strategies to better define the role of these neurons in body weight maintenance 4 . The authors found that deleting Lepr expression from Glp1r + cells stimulated weight gain through overeating.…”
Section: Discussionmentioning
confidence: 99%
“…However, no such rescue occurred if GABAergic Glp1r + neurons were excluded from the Lepr reactivation, indicating that leptin acts on GABAergic Glp1r + neurons to control feeding and body weight. Importantly, a similar knockout and conditional reactivation approach showed that expressing Glp1r only in GABAergic Lepr + cells was sufficient for liraglutide to suppress appetite 4 . The study concluded that the likely site of interaction of liraglutide and leptin was the DMH given the abundance of leptin-sensing Glp1r + neurons there 4 .…”
Section: Discussionmentioning
confidence: 99%